The Women, Peace and Security Agenda - Míla O'Sullivan (Czech Journal of International Relations, 2019)
The adoption of the United Nations Security Council Resolution 1325 on women, peace and security (WPS) in 2000 has prompted the development of an extensive WPS scholarship within the field of feminist International Relations. The dynamic scholarly debate is characterised by certain tensions between two feminist groups – the radical revolutionary one which advocates a redefinition of the global order and is more sceptical of the agenda, and the pragmatist one accentuating the compromise towards the existing peace and security governance. This article explores the two main subjects of the WPS research – the discourse and implementation, as they have been informed by the revolutionary and pragmatist approaches. The article shows that while the academic inquiries into the WPS discourse reveal disappointment with the compromises made regarding the revolutionary vision, this disappointment is also present in the literature on implementation. The latter literature nonetheless acknowledges feminist pragmatism as a way forward given the realities on the ground.